Peritoneal Dialysis -Associated Fibrosis: Emerging Mechanisms and Therapeutic Opportunities - Prasad, Narayan; Chaturvedi, Saurabh; Singh, Harshit; Udumula, Mary Priyanka; Rawat, Atul; Jeyakumar, Meyyappan; Jaiswal, Akhilesh; Kumar, Sachin; Agarwal, Vikas (Frontiers in Pharmacology, 2025)
Peritoneal Dialysis (PD) requires a healthy and functional peritoneal membrane for adequate ultrafiltration and fluid balance, making it a vital treatment for patients with end-stage renal disease (ESRD). The spectrum of PD-associated peritoneal fibrosis encompasses a diverse range of collective mechanisms: peritoneal fibrogenesis, epithelial to mesenchymal transition (EMT), peritonitis, angiogenesis, sub-mesothelial immune cells infiltration, and collagen deposition in the sub-mesothelial compact zone of the membrane that accompany deteriorating membrane function. In this narrative review, we summarize the repertoire of current knowledge about the structure, function, and pathophysiology of the peritoneal membrane, focusing on biomolecular mechanisms and signalling pathways that potentiate the development and progression of peritoneal fibrosis. The article suggests future directions that could enhance our comprehension of the relationship between peritoneal membrane dysfunction and its fibrosis to elucidate the promising targets for therapeutic interventions. A thorough understanding of early events in pathophysiology closely associated with the inflammatory events in peritoneal fibrosis is the logical starting point for identifying new targets rather than concentrating on more downstream effects. Biomarkers are essential for monitoring the progression of peritoneal fibrosis and evaluating the effectiveness of therapeutic interventions. Biomarkers are evolving in concert with new targets and novel agents, and biomarker outcomes offer a means of monitoring the peritoneal membrane’s health. Recent approaches to reducing the etiologies of peritoneal membrane dysfunction, the impact of fibroblast switch, and peritoneal membrane events perturbing fibroblast function are explored and suggest using unique, effective therapeutic strategies to target peritoneal fibrosis and associated complications.